Crystal structures of a molecule designed not to pack tightly - Kohl, Bernd; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2015)
Abstract Organic molecules of intrinsic microporosity (OMIMs) are structurally constructed to not pack tightly. Consequently, only weak interactions between OMIM molecules can occur, which is the reason that almost all OMIMs have been described and investigated in their amorphous states. For the same reason it is very difficult to grow single crystals of OMIMs for X-ray structural analysis. Here we describe four different polymorphs of an OMIM that was before only described in the amorphous state.